Statistical Optimization of Blending Conditions and Performance Evaluation of Optimal Bio-Asphalt Content - T.H., Varun Kumar; Mayakrishnan, Muthukumar; Somasundaram, Murugavelh (Salehan Institute of Higher Education, 2025)
To mitigate environmental impacts and promote sustainability in highway construction, this study investigates the optimization of blending conditions and the performance evaluation of bio-modified asphalt binder incorporating bio-asphalt derived from the pyrolysis of waste cooking oil (WCO) and low-density polyethylene (LDPE). A response surface approach was employed to optimize key blending parameters—temperature, speed, and time—based on critical physical properties of the binder. Furthermore, the optimized bio-asphalt binder was further evaluated through rheological performance tests (multiple stress creep recovery and linear amplitude sweep) and mechanical performance tests (Marshall stability, tensile strength ratio, resilient modulus, indirect tensile fatigue, and dynamic creep). The optimal conditions were identified as 130°C, 1000 rpm, and 42.37 min. Statistical validation using ANOVA, residual analysis, leverage, and Cook’s distance confirmed the model’s reliability, with prediction errors remaining below 5%. The bio-modified asphalt binder exhibited enhanced elastic recovery and reduced non-recoverable creep compliance (Jnr), indicating superior resistance to permanent deformation in comparison with the control asphalt binder. Additionally, the bio-modified asphalt mixture demonstrates superior Marshall stability, resilient modulus, tensile strength ratio, retained stability, and resistance to deformation in comparison with the control asphalt binder. These results demonstrate the potential of bio-asphalt as a viable, eco-friendly modifier for asphalt binders in tropical climates.